A novel neutrophil extracellular trap signature to predict prognosis and immunotherapy response in head and neck squamous cell carcinoma - Li, Qilin; Chen, Weimin; Li, Qiuhui; Mao, Jing; Chen, Xin (Frontiers in Immunology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignant cancers, and the patients with HNSCC possess early metastases and poor prognosis. Systematic therapies (including chemotherapy, targeted therapy and immunotherapy) are generally applied in the advanced/late stages of HNSCC, but primary and acquired resistance eventually occur. At present, reliable biomarkers to predict prognosis of HNSCC are not completely identified. Recent studies have shown that neutrophil extracellular traps (NETs) are implicated in cancer progression, metastasis and cancer immune response, and NETs-related gene signatures are associated with patients’ prognosis in several human cancers. To explore whether NETs-related genes play crucial roles in HNSCC, we have performed systematic analysis and have several findings in the current study. Firstly, we identified 7 novel NETs-related genes and developed a NETs-score signature, which were highly associated with clinicopathological and immune traits of the HNSCC patients. Then, we, for the first time, uncovered that NIFK was significantly upregulated in HNSCC patient samples, and its levels were significantly linked to tumor malignancy and immune status. Moreover, functional experiments validated that NIFK was required for HNSCC cells proliferation and metastasis. Altogether, this study has identified a novel NETs-score signature based on 7 novel NETs-related genes to predict prognosis of HNSCC and NIFK also has explored a new way for personalized chemo-/immuno- therapy of HNSCC.